Peran Lembaga Adat Melayu Roai Kabupaten Rokan Hulu dalam Melestarikan Budatya Melayu Riau - asriani, devi; Sutrisno, Imam Hadi; Anis, Madhan (Program Studi Pendidikan Sejarah - Universitas Samudra, 2022)
The writing in this article aims to examine the role of the Riau Malay Customary Institution in Rokan Hulu Regency in the traditional values ​​of Malay culture. This study discusses the role of the Riau Malay Customary Institution in Rokan Hulu district with Malay cultural values ​​in 2009-2021. The method used is field research or field research in the form of qualitative descriptive with an anthropological approach using ethnographic methods. Based on Key's research that regarding the role of Malay traditional institutions in Rokan Hulu Regency, it can unlock that the role of Malay adat institutions in Rokan Hulu Regency is to fight for the rights of indigenous peoples in Rokan Hulu Regency, as a forum for channeling the aspirations of the Malay community, especially Rokan Hulu Regency and fighting for the rights of the people of Rokan Hulu Regency. - the rights of indigenous peoples such as customary land. This research shows the role of the Riau Malay Customary Institution in Rokan Hulu Regency, namely the development of traditional leaders. The efforts of the Malay Traditional Institution of Rokan Hulu Regency are to use operational strategies and cooperation between organizations such as Hulubalang. The operational strategy of the Malay Traditional Institution of Rokan Hulu Regency is by providing guidance to traditional leaders and also trying to publicize all forms of activities of the Rokan Hulu Regency Malay Traditional Institution through existing media.